From slavery to freedom a history of African Americans - Franklin, John Hope 1915-2009 (McGraw-Hill, 1994)
This work charts the journey of African Americans from their origins in the civilizations of Africa, through slavery in the Western Hemisphere, to their struggle for freedom in the West Indies, Latin America and the United States.